Characterization and Cytotoxic of Synthesized Silver Nanoparticles by Using the Ocimum basilicum - Jenan Atiyah Ghafil (World Journal of Experimental Biosciences, 2018)
The preparation of nanomaterial using herbal plants is considered one of the most effective methods. The preparation of nanoscale silver nitrate based on plant herbs will open new horizons in the safe synthesis of nanomaterial. The current study highlighted the green synthesis of silver nanoparticles (AgNPs) using the Ocimum basilicum (aqueous extract). Here, AgNPs were green synthesized by the precipitation method based on the reduction of silver ions (AgNO3) by O. basilicum extract. The toxicity effects of green synthetic AgNPs were evaluated by using a micronucleus assay, the effect on mice’s liver and kidney, and lethal dose 50 (LD 50) post administrated to experimental mice with AgNPs orally. The green synthesized AgNPs were relatively uniform in size in the range of 25-70 nm. The results demonstrated that there is no significant effect of green synthetic AgNPs on the number of polychromatic erythrocytes of micronuclei cells. The 1 mg of green synthetic AgNPs killed 50 % of experimental mice (LD 50= 1 mg/100 mg of mice weight). The results showed that O. basilicum extract has a good ability to produce safe silver nanoparticles.
Keywords: AgNPs, Kidney, Liver, Micronucleus assay, Mice.